2022
DOI: 10.1007/s10806-022-09881-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental Values on Consumer Intentions to Participate in Agritourism—A Model to Extend TPB

Abstract: This study examines the influence of environmental values on consumer intentions to participate in agritourism through the theory of planned behaviour (TPB) and value-belief-norm (VBN) theory. It proposes an integrative model by adding two variables, i.e., environmental benefits and the human-nature coordination concept, to the TPB. The study employs a questionnaire survey method and a sample of 640, which was statistically analysed through structural equation modeling (SEM). The results reveal that the “envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Pollution-free environment and low prices may be the two main strategies for the agro-tourism industry to attract customers. Zhao et al (2022) noted that customer behaviors toward agro-tourism are influenced by their attitude, subjective norms and PBC. Yet, the carbon mitigation attitude in exploring customer’s intentions and behaviors has not received much attention in agro-tourism segment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pollution-free environment and low prices may be the two main strategies for the agro-tourism industry to attract customers. Zhao et al (2022) noted that customer behaviors toward agro-tourism are influenced by their attitude, subjective norms and PBC. Yet, the carbon mitigation attitude in exploring customer’s intentions and behaviors has not received much attention in agro-tourism segment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literatures have mainly focused on agro-tourism satisfaction (Lachnidaki et al, 2021;Hussein and Rohman, 2021), agro-tourism service quality dimensions (Mulyo et al, 2021;Andayani et al, 2021) and agro-tourism development (Kubickova and Campbell, 2020;Rasulovich, 2021). However, several previous studies have examined the factors influencing behavioral intentions and actual behaviors toward agro-tourism, where Nakpathom and Pitchayadejanant (2017) have explored the determinants that affect visitor's intentions toward agro-tourism, Nguyen et al (2018) have identified that residents' attitudes have significant impact on their behaviors toward agro-tourism, Nishshanka et al (2019) have noted that tourists' attitude influences their willingness toward agro-tourism, Fern andez-Hern andez et al (2016) have mentioned that environmental concerns substantially influence visitors' behaviors toward agro-tourism, Zhao et al (2022) have stressed that attitudes and subjective norms have significant impacts on customers' intentions to participate in agrotourism, Zhong et al (2022) have measured that perceived value significantly influences farmer's green production and Suhud et al (2022) have examined the link between perceived value and behavioral intentions and found that perceived value has a significant effect on travel intentions in the coffee tourism perspective. Nevertheless, to the best knowledge, no previous study has examined the effects of carbon mitigation attitude, energy saving norms and perceived hygiene value on behavioral intentions and actual behaviors in agro-tourism settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the existing tourism literature, the VBN theory has been employed in various contexts to explain the pro-environmental behavior of museum vacationers [ 53 ], adventure tourists [ 54 ] and visitors to green accommodation [ 51 ], national parks [ 55 ] and conservation areas [ 56 ], sustainable transportation [ 57 ] and towel reuse intention [ 58 ]. In recent studies, Megeirhi et al [ 59 ] applied the VBN theory to sustainable heritage tourism and Zinan Zhao et al [ 60 ] examined agritourism consumer intentions by combining VBN and planned behavior theories. Due to environmental concerns and a sense of moral responsibility, tourists today tend to adopt a sustainable mindset.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Climate change awareness refers to the ability of individuals to recognize the nature of climate change problems, that is, awareness of temperature rises, sea level rises, extreme weather, and global warming [37]. The awareness of climate change among individuals helps to reduce different environmental problems [38,39]. In recent years, a growing number of scholars have realized that farmers are often rational in specific climate change risk scenarios.…”
Section: Theoretical Analysis and Research Assumptionsmentioning
confidence: 99%